Modular polylactic acid microparticle‐based scaffolds prepared via microfluidic emulsion/solvent displacement process: Fabrication, characterization, and in vitro mesenchymal stem cells interaction study1. Issue 3 (31st August 2012) - Salerno, A.; Levato, R.; Mateos‐Timoneda, M. A.; Engel, E.; Netti, P. A.; Planell, J. A.
Abstract: The present study reports a novel approach for the design and fabrication of polylactic acid (PLA) microparticle‐based scaffolds with microstructural properties suitable for bone and cartilage regeneration. Macroporous PLA scaffolds with controlled shape were fabricated by means of a semicontinuous process involving (1) microfluidic emulsification of a PLA/ethyl lactate solution (5% w/v) in a span 80/paraffin oil solution (3% v/v) followed by (2) particles coagulation/assembly in an acetone/water solution for the development of a continuous matrix. Porous scaffolds prepared from particles with monomodal or bimodal size distribution, overall porosity ranges from 93 to 96%, interparticles porosity from 41 to 54%, and static compression moduli from 0.3 to 1.4 MPa were manufactured by means of flow rate modulation of of the continuous phase during emulsion. The biological response of the scaffolds was assessed in vitro by using bone marrow‐derived rat mesenchymal stem cells (MSCs). The results demonstrated the ability of the scaffolds to support the extensive and uniform three‐dimensional adhesion, colonization, and proliferation of MSCs within the entire construct. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 720–732, 2013.